ETIKA BERMEDIA SOSIAL DALAM MENYIKAPI PEMBERITAAN BOHONG (HOAX) PERSPEKTIF HADIS - Al-Ayyubi, M. Zia (UIN Sunan Kalijaga Yogyakarta, 2018)
This paper will discusses about the troubling phenomenathat occur in cyberspace, precisely on social media. The negative contents are found, both attacking groups, and individuals.The attack usually uses content in the form of provocation, slander, hate speech, hoaxes, appealing opinions that lead to defamation, etc. The problem above, if we examine its historicity in Islamic history, it turns out that this phenomena has been happening since the early days of Islam. Precisely, one of the prophet's wives, Siti Aisyah, who was accused of committing adultery with one of the war soldiers. Then the incident became the cause of the revelation baraâ€™ahâ€™s letter. Back then, the kind of news mentioned above was disseminated by transmission media. In the present, it is disseminated with social media which is even faster in its flow of transmission. So the term viral appears. The offer submitted in this paper is the attitude and ethics of every netizens in social media with a hadith approach. So that it can be finally in accordance with the with the portion and proportion in utilizing a social media.Â Keyword: Hermeneutics Hadis, Etics, Social Media, Hoax.